Exploring barriers and facilitators to water availability and accessibility, and potential strategies for improving water accessibility and children’s intake in family childcare homes: a qualitative study - Gans, Kim M.; Chacón, Violeta; Warykas, Sarah Wen; Baird, Madeline; Esquivel, Vanessa; Zhang, Suge; Tovar, Alison; Ray, Snehaa; Inman, Naomi; McCauley, Peter; Zambrano Rodriguez, Viviana C.; Miller, Michelle; et al. (Frontiers in Nutrition, 2025)
BackgroundChildren in the U.S. drink too little water and too much juice and sugar sweetened beverages. Inadequate access to drinking water in locations where children spend substantial time, like family childcare homes (FCCH) could play a role in low child water intake. The aim of this qualitative study was to explore barriers and facilitators to water availability and accessibility in FCCH, and determine potential strategies for facilitating water accessibility and children’s intake in FCCH.MethodsWe conducted virtual interviews, in Spanish and/or English, with family child care providers (FCCP) from Rhode Island, Connecticut, and Massachusetts. Interviews were conducted by University of Connecticut graduate students, including two who were fluent in Spanish and English. These were audio-recorded, transcribed verbatim, and translated to English. We conducted a deductive analysis using a priori themes. Additional codes were developed and applied to capture emerging themes from the qualitative data.ResultsTwenty FCCP (100% identified as female; 50% as Latina) participated in the interviews. FCCP barriers to water availability at FCCH included focus on other beverages, e.g., milk; confusion with the Child and Adult Care Food Program (CACFP) guidelines regarding water, and concerns about: water quality, mess, children eating enough food/milk, bathroom accidents, and cost for filters/bottled water. Barriers to children drinking water included: children not liking or preferring water, parental preferences/role modeling, and parental concerns about water quality. Suggested potential strategies to facilitate water access and intake included water filters to ensure safe water access, self-serving stations and water bottles to encourage autonomy among children, and incorporating water into daily routines. Participants also favored materials and activities to educate and encourage children to drink water and to keep track of their intake.ConclusionThese findings suggest that interventions to increase water consumption at FCCH should provide resources to guarantee safe water access to children, encourage children to drink water, and help clarify misperceptions and confusion around CACFP beverage guidelines. Future research should evaluate the effectiveness of interventions to provide education and water access resources to FCCP and families on improving child water access, availability and intake.